Transfer of 40K, 226Ra and 210Pb from soil to plants in various locations of El-Jadida agricultural area (north-western Morocco) - El Aouidi Samira (EDP Sciences, 2021)
The present study examines the radionuclides (40K, 226Ra and 210Pb) concentrations in soil and plants collected from El Jadida agricultural area. The transfer factors of radionuclides from the soil to different components of the plants (stems, roots, leaves, and fruits) was also determined and assessed. The plants include various vegetable crops, including pumpkin, zucchini, beans, fennel, potato, sunflower, broccoli, onion, carrot, cabbage, tomato, and mallow from three different locations. A wide-range HPGe gamma-ray spectrometer is used for radionuclide activity measurement. The radionuclides activities of soil samples display a wide range of variability from one location to another. The concentrations of 226Ra vary between 18 ± 1 Bq.Kg-1 and 80 ± 4 Bq.Kg-1, the concentrations of 210Pb range from 49.7 ± 4.4 Bq.Kg-1 to 269 ± 16 Bq.Kg-1, and the 40K values fluctuate between 94,1 ± 6,5 and 286,1 ± 15,3 Bq.Kg-1. The study showed that the transfer factor for K-40 is more significant than Pb-210 and Ra-226, mainly related to the use of fertilizers rich in potassium in the agricultural areas, leading to its concentrations increase.